2018
DOI: 10.1016/j.ejmech.2017.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-containing ecdysteroid derivatives vs. multi-drug resistance in cancer: Preparation and antitumor activity of oximes, oxime ethers and a lactam

Abstract: Multidrug resistance is a widespread problem among various diseases and cancer is no exception. We had previously described the chemo-sensitizing activity of ecdysteroid derivatives with low polarity on drug susceptible and multi-drug resistant (MDR) cancer cells. We have also shown that these molecules have a marked selectivity towards the MDR cells. Recent studies on the oximation of various steroid derivatives indicated remarkable increase in their antitumor activity, but there is no related bioactivity dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…The detected Δδ = 4.2 ppm syn ‐ anti parameter on the C‐21 signal in compound 3 is in good agreement with our results on C‐6 oxime derivatives of ecdysteroids and unambiguously confirmed the NMR differentiation of the E / Z isomers. Considering the detected δC‐21 (17 ppm) in compounds 6 and 7 , we can conclude that these compounds are also 20( E )‐oxime derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detected Δδ = 4.2 ppm syn ‐ anti parameter on the C‐21 signal in compound 3 is in good agreement with our results on C‐6 oxime derivatives of ecdysteroids and unambiguously confirmed the NMR differentiation of the E / Z isomers. Considering the detected δC‐21 (17 ppm) in compounds 6 and 7 , we can conclude that these compounds are also 20( E )‐oxime derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, several poststerone derivatives, containing a substituted dioxolane (e.g., acetonide) moiety connected to their A‐ring, were found to be free from the efflux pump inhibitory activity, while acting as strong chemo‐sensitizers in combination with doxorubicin . In addition to this, ecdysteroid 6‐oximes and oxime ethers demonstrated markedly increased ABCB1 inhibitory activity, while acting as similarly potent chemo‐sensitizers as their corresponding 6‐oxo analogs …”
Section: Introductionmentioning
confidence: 99%
“…In the context of this latter strategy, our group has investigated certain structure–activity relationships to explore the effect of these compounds on the drug resistance of cancer cell lines. 11 14 …”
mentioning
confidence: 99%
“…From our previous extensive structure-activity relationship studies on the antitumor properties of ecdysteroids we found that their multidrug resistance decreasing activity does not rely on Pgp inhibition [9][10][11][12]. Because of this, our research on new antitumor ecdysteroid derivatives focuses on compounds that exert their activity without directly affecting drug efflux, and, as such, are free from the many potential problems (e.g., unwanted drug-drug interactions, altered pharmacokinetics of co-administered antitumor drugs, etc.)…”
Section: Introductionmentioning
confidence: 99%